Wired on Steroids: Sexual Differentiation of the Brain and Its Role in the Expression of Sexual Partner Preferences - Alexander, Brenda M.; Skinner, Donal C.; Roselli, Charles E. (Frontiers in Endocrinology, 2011)
The preference to seek out a sexual partner of the opposite sex is robust and ensures reproduction and survival of the species. Development of female-directed partner preference in the male is dependent on exposure of the developing brain to gonadal steroids synthesized during critical periods of sexual differentiation of the central nervous system. In the absence of androgen exposure, a male-directed partner preference develops. The development and expression of sexual partner preference has been extensively studied in rats, ferrets, and sheep model systems. From these models it is clear that gonadal testosterone, often through estrogenic metabolites, cause both masculinization and defeminization of behavior during critical periods of brain development. Changes in the steroid environment during these critical periods results in atypical sexual partner preference. In this manuscript, we review the major findings which support the hypothesis that the organizational actions of sex steroids are responsible for sexual differentiation of sexual partner preferences in select non-human species. We also explore how this information has helped to frame our understanding of the biological influences on human sexual orientation and gender identity.